CONSIDERATION OF THE DYNAMICS OF INDUSTRIAL PRODUCTION IN THE EVALUATION OF ENERGY SAVING POTENTIAL AT THE LEVEL OF INDIVIDUAL COUNTRIES AND REGIONS - N. A. Kislenko; I. S. Kopylova; N. V. Malanicheva (Вестник университета)
An approach to the allocation of economic and macroeconomic factors, affecting the final energy consumption, taking into account the seasonal unevenness of industrial production and the inertia of changes in the production of final products relative to the consumption of energy required for their production, has been considered in the article. In addition, factors have been reviewed not only at the end of the value chain on the basis of gas-consuming industries, but also taking into account the indicators of the raw material sector of the economy, which determines the beginning of the value chain.